The influence of mathematical disposition on high school students' understanding of mathematical concepts - Hanifatul Aini; Nanang Khuzaini (UNION : Jurnal Ilmiah Pendidikan Matematika, 2024)
One of the subjects often considered challenging by students is mathematics, leading to difficulties in learning the subject. This is due to students' lack of ability to comprehend mathematical concepts. This research investigates the influence of mathematical disposition on the mathematical concept understanding of high school students. The study utilizes a correlational survey method with a quantitative approach. The study employs a quantitative approach with a correlational survey method. The population includes all twelfth-grade science students at SMA Negeri 1 Sedayu. The sampling technique utilizes random sampling, with a sample size of 65 students selected from two twelfth-grade science classes. The instruments used in the research consist of a mathematical disposition questionnaire and an essay test on the ability to understand mathematical concepts. Data analysis is performed through classical assumption tests and simple regression analysis. The classical assumption tests include normality and linearity tests. The results indicate a significant positive influence of mathematical disposition on students' understanding of mathematical concepts, with a contribution of mathematical disposition to the understanding of mathematical concepts amounting to 34.8%.